A Time Log Study of Activities of Medical Officers Working at Urban Health Centres of Ahmedabad City, Gujarat - Gneyaa Bhatt; Anushka Patel (Indian Association of Preventive and Social Medicine, 2021)
Introduction: Medical Officer (MO) of an Urban Health Centre (UHC) is responsible for implementing all activities grouped under Health and Family Welfare delivery system in UHC area. While RBSK MO of UHC works under Rashtriya Bal Swasthya Karyakaram (RBSK). Objective: To assess various activities carried out by MBBS MOs and RBSK MOs at UHCs with proportion of time spent on each of activities. Method: The study was conducted at randomly selected 12 UHCs from randomly selected 3 zones of Ahmedabad city. Data regarding activities of MBBS and RBSK MOs were collected using predesigned matrix time log sheet wherein the MOs had to fill up their activities on 15 minutes slots for 2 weeks. Data were entered and analyzed using MS Excel. Results: Effective working time per day was 7 + 1/2 hours &6+1 hours for an MBBS & RBSK MO respectively. Majority of time spent per day by the MBBS MO was in conducting general OPD (mean 149 minutes) followed by preparing/checking reports. While, for RBSK MO, it was in health checkup at Anganwadis & Schools(118& 93 minutes respectively) followed by preparation of reports. Both MOs spent maximum time towards clinical work (48.51% by MBBS& 68.45% RBSK MOs) followed by administrative work (33.73% by MBBS & 18% by RBSK), field visits (11.5% by both), CME/workshops/trainings (2.02% by MBBS and 0.66% by RBSK) and other activities (4.2% by MBBS and 0.8% by RBSK). Conclusion: Frequency of various major activities was as per the recommendations for most of the MOs. However, many of them were not able to cover all the activities mentioned under guidelines.